Huscher, Cloud County - Theres, Dionysis (Kansas State University, The Chapman Center for Rural Studies, 2012)
The author uses geographical concepts and relates them to the rise and fall of Huscher, Kansas. He utilizes historic documents, genealogical data, census records, and historic maps to reconstruct the history of the town.
Dionysis Theres, “Huscher, Cloud County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/84.
Keywords: Cloud County; Sante Fe Railroad; Concordia; David Huscher; Center Township; Bossemeyer Brothers